2021
DOI: 10.1002/stem.3392
|View full text |Cite
|
Sign up to set email alerts
|

miR-351-3p Promotes Rat Amniotic Fluid-Derived Mesenchymal Stromal Cell Proliferation via Targeting the Coding Sequence of Abca4

Abstract: Amniotic fluid-derived mesenchymal stromal cells (AFMSCs) present different features, depending on the isolation timing and culture conditions. The lack of uniform experimental standards hinders the comparison of results from different studies on AFMSCs. Moreover, understanding the molecular mechanisms that underlie the features of AFMSCs isolated at different embryonic developmental stages might allow the obtention of more viable and highly proliferative AFMSCs through genetic modification. We isolated AFMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Differentiation of AFSCs is regulated by DNA methylation, histone modification, and the expression of small non-coding RNAs, [28] most notably the miR-351-3p, a gene that targets Abca4 (ATP-binding cassette transporter A4, Abca4) and regulates the proliferation and migration of AFSCs by targeting the 3 0 -UTR (untranslated region, UTR) of Chrdl1 (chordin-like 1, Chrdl1) and downregulating its expression. [29,30] Reports have shown that AFSCs grow well in a serum-free medium, and the proliferation efficiency was higher in the AmnioMAX medium than in Dulbecco's modified Eagle medium. [12,31] The cells have a doubling time of about 36 h, can proliferate 250 times in vitro without chromosome loss, [3] and maintain stable telomere lengths over several generations.…”
Section: Biological Properties Of Afscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiation of AFSCs is regulated by DNA methylation, histone modification, and the expression of small non-coding RNAs, [28] most notably the miR-351-3p, a gene that targets Abca4 (ATP-binding cassette transporter A4, Abca4) and regulates the proliferation and migration of AFSCs by targeting the 3 0 -UTR (untranslated region, UTR) of Chrdl1 (chordin-like 1, Chrdl1) and downregulating its expression. [29,30] Reports have shown that AFSCs grow well in a serum-free medium, and the proliferation efficiency was higher in the AmnioMAX medium than in Dulbecco's modified Eagle medium. [12,31] The cells have a doubling time of about 36 h, can proliferate 250 times in vitro without chromosome loss, [3] and maintain stable telomere lengths over several generations.…”
Section: Biological Properties Of Afscsmentioning
confidence: 99%
“…The phenotypic characteristics of AFSCs vary with the stage of pregnancy, [3] and epigenetic modifications guide AFSC differentiation into multiple lineages, playing a vital role in stem cell fate determination. Differentiation of AFSCs is regulated by DNA methylation, histone modification, and the expression of small non-coding RNAs, [28] most notably the miR-351-3p, a gene that targets Abca4 (ATP-binding cassette transporter A4, Abca4) and regulates the proliferation and migration of AFSCs by targeting the 3′-UTR (untranslated region, UTR) of Chrdl1 (chordin-like 1,Chrdl1) and downregulating its expression [29,30] …”
Section: Biological Properties Of Afscsmentioning
confidence: 99%
“…MSCs can be isolated from different adult tissues such as umbilical cord blood, bone marrow, adipose tissue, placenta, amniotic fluid, urine and other tissues. 7 , 8 , 9 , 10 , 11 They express low levels of major histocompatibility complex (MHC) class I molecules and MHC class II molecules, which enable them to have low immunogenicity. 12 In vitro, MSCs can differentiate into a range of cell types, including adipocytes, osteocytes, hepatocytes, chondrocytes, muscle, vascular smooth muscle cells and other connective tissues.…”
Section: Introductionmentioning
confidence: 99%